Impact of Clinical Experience and Diagnostic Performance in Patients with Acute Abdominal Pain - Helena Laurell; Lars-Erik Hansson; Ulf Gunnarsson (Gastroenterology Research and Practice)
Background. The aims were to evaluate the importance of the formal competence of the emergency department physician, the patient’s time of arrival at the emergency department, and the use of a structured schedule for investigation of patients with acute abdominal pain. Methods. Patients attending the Mora Hospital with acute abdominal pain from 1997 to 2000 were registered prospectively according to a structured schedule. Registration included history, symptoms, signs, preliminary diagnosis, surgery and final diagnosis after at least one year.  Results. 3073 acute abdominal pain patients were included. The preliminary diagnosis, as compared with the final diagnosis, was correct in 54% (n=1659). Previously, during 1996, a base-line registration of 790 patients had a 58% correct diagnoses  (n=458). A majority of the patients (n=2699; 88%) were managed by nonspecialists. The proportion of correct diagnoses was 54% (n=759) for pre-registrar house officers and 55% (n=443) for senior house officers. Diagnostic performance at the emergency department was independent of patient’s time of arrival. Conclusions. A structured schedule for investigation did not improve the diagnostic precision at the emergency department in patients with acute abdominal pain. The diagnostic performance was independent of the formal competence of the physician and the patient's time of arrival.